Arsenic in the Iberoamerican Region: The Iberoarsen Network and a possible economic solution for arsenic removal in isolated rural zones - Morgada, Maria Eugenia; Mateu, Miguel; Bundschuh, Jochen; Litter, Marta Irene (Sociedad Geológica de Portugal, 2008)
Fil: Morgada, Maria Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica; Argentina